1983
DOI: 10.3171/jns.1983.58.6.0949
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance and development of cerebral aneurysms in moyamoya disease

Abstract: The authors report a case of multiple cerebral aneurysms associated with moyamoya disease, in which the reduction and disappearance of bilateral internal carotid artery aneurysms and the new development and enlargement of bisilar artery aneurysms were demonstrated on sequential cerebral angiograms. Possible mechanisms of the spontaneous disappearance and development of cerebral aneurysms in association with moyamoya disease are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…This procedure may reduce pathologic blood flow by improving both the blood flow and perfusion pressure in the MCA territory, which would consequently constrict moyamoya arteries and possibly shrink distal aneurysms. 6 In these two patients, the anastomosis improved cerebral hemodynamics as measured by CT perfusion and the aneurysm was shown by DSA to have vanished, accompanied by deceased moyamoya vessels. This suggests that patients with developed collateral circulation following revascularization are at lower risk of aneurysmal rebleeding from the peripheral moyamoya vessels.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This procedure may reduce pathologic blood flow by improving both the blood flow and perfusion pressure in the MCA territory, which would consequently constrict moyamoya arteries and possibly shrink distal aneurysms. 6 In these two patients, the anastomosis improved cerebral hemodynamics as measured by CT perfusion and the aneurysm was shown by DSA to have vanished, accompanied by deceased moyamoya vessels. This suggests that patients with developed collateral circulation following revascularization are at lower risk of aneurysmal rebleeding from the peripheral moyamoya vessels.…”
Section: Discussionmentioning
confidence: 77%
“…5 Peripheral aneurysms are caused by rupture of the pathological vessels that form a hematoma, and are regarded as pseudo-aneurysms due to their transient appearance on cerebral angiograms. 6 Rupture occurs due to persistent hemodynamic stress on dilated, fragile moyamoya vessels, 7 often occurring in the basal ganglia, thalamus or ventricles. 8 Major artery aneurysms grow slowly and do not disappear; they are often discovered around the circle of Willis.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have considered these lesions to be pseudoaneurysms. Aneu- rysms associated with moyamoya show differences in their evolution and location when compared with those in the general population [10][11][12]. However, clinical differ ences between the aneurysms in unilateral and bilateral moyamoya remain unclarified.…”
Section: Introductionmentioning
confidence: 99%
“…However, Satoh et al reported a case of MMD associated with bilateral PcomA aneurysm, in which the aneurysms did not rupture during the 2-year follow-up period. MMD progressed and the ICA was occluded, resulting in involvement of the bilateral PcomA and disappearance of the PcomA aneurysms (9). Adams et al reported one case of MMD with PcomA aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, the PcomA will suffer from too much blood flow, possibly resulting in the formation of an aneurysm (7). Expansion of the PcomA with aneurysm after MMD formation is rare, and only a few cases have been reported (1, 8,9,10). Therefore, study on the treatment and prognosis of this condition has been limited.…”
Section: öZmentioning
confidence: 99%